Polyadenylation of the Xenopus beta 1 globin mRNA at a downstream minor site in the absence of the major site and utilization of an AAUACA polyadenylation signal. - Mason, P J (1985)
We show that adult reticulocytes of Xenopus laevis produce two forms of the beta 1 globin mRNA that differ in their site of polyadenylation. The minor site of polyadenylation is located 46 nucleotides downstream of the major site and is used in approximately 1% of mRNA molecules. A fusion gene was constructed containing the promoter from the thymidine kinase gene of herpes simplex virus fused to the protein coding, 3'-noncoding and 3'-flanking sequences of the X. laevis beta 1 globin gene. When injected into the nuclei of Xenopus oocytes, transcripts of this fusion gene were accurately and efficiently spliced and polyadenylated. The proportion of fusion gene transcripts terminating at the major and minor polyadenylation sites after injection into oocytes was approximately similar to that found in reticulocytes. When the AATAAA sequence element upstream from the major site was deleted, the minor site was used with a high (greater than 90%) efficiency. Therefore, by comparing the ratio of polyadenylation at the major and minor sites, it is possible to determine the effect of sequence alterations at the major site. In a construct where the AATAAA polyadenylation signal was changed to AATACA a high proportion (35%) of transcripts continued to be polyadenylated at the major site. This suggests a surprisingly high degree of flexibility in the precise polyadenylation signal.